Cancer chemoprevention with nuts. - Falasca, Marco; Casari, I.; Maffucci, T. (2014)
It is well established that increased nut consumption is associated with a reduced risk of major chronic diseases, such as cardiovascular disease and type 2 diabetes mellitus. On the other hand, the association between nut consumption and cancer mortality is less clear. Recent studies have suggested that nut consumption is associated with reduced cancer mortality. This evidence reinforces the interest to investigate the chemopreventive properties of nuts, and it raises questions about the specific cancer type(s) and setting that can be more affected by nut consumption, as well as the cellular mechanisms involved in this protective effect. Here we discuss recent studies on the association of nut consumption and cancer, and we propose specific cellular mechanisms by which nut components can affect cancer progression.